Industrial development in Africa : mapping industrialization pathways for a leaping leopard - Abegaz, Berhanu (Routledge, 2018)
Industrial Development in Africa critically synthesizes and reframes the debates on African industrial development in a capability-opportunity framework. It recasts the challenge in a broader comparative context of successive waves of catchup industrialization experiences in the European periphery, Latin America, and East Asia. Berhanu Abegaz explores the case for resource-based and factor-based industrialization in North Africa and Sub-Saharan Africa by drawing on insights from the history of industrialization, development economics, political economy, and institutional economics. Unpacking complex and diverse experiences, the chapters look at Africa at several levels: continent-wide, sub-regions on both sides of the Sahara, and present analytical case studies of 12 representative countries: Egypt, Tunisia, Ethiopia, Kenya, Tanzania, Mauritius, Zimbabwe, South Africa, Ghana, Nigeria, Senegal, and Cote d'Ivoire. Industrial Development in Africa will be of interest to undergraduate and graduate students studying African development, African economics, and late-stage industrialization. The book will also be of interest to policymakers.